Drosophila as a Model for Intractable Epilepsy: Gilgamesh Suppresses Seizures in parabss1 Heterozygote Flies. - Howlett, I.C.; Rusan, Z.M.; Parker, L.; Tanouye, M.A. (G3 : genes - genomes - genetics, 2013)
Intractable epilepsies, that is, seizure disorders that do not respond to currently available therapies, are difficult, often tragic, neurological disorders. Na(+) channelopathies have been implicated in some intractable epilepsies, including Dravet syndrome (Dravet 1978), but little progress has been forthcoming in therapeutics. Here we examine a Drosophila model for intractable epilepsy, the Na(+) channel gain-of-function mutant para(bss1) that resembles Dravet syndrome in some aspects (parker et al. 2011a). In particular, we identify second-site mutations that interact with para(bss1), seizure enhancers, and seizure suppressors. We describe one seizure-enhancer mutation named charlatan (chn). The chn gene normally encodes an Neuron-Restrictive Silencer Factor/RE1-Silencing Transcription factor transcriptional repressor of neuronal-specific genes. We identify a second-site seizure-suppressor mutation, gilgamesh (gish), that reduces the severity of several seizure-like phenotypes of para(bss1)/+ heterozygotes. The gish gene normally encodes the Drosophila ortholog of casein kinase CK1g3, a member of the CK1 family of serine-threonine kinases. We suggest that CK1g3 is an unexpected but promising new target for seizure therapeutics.